Influence of Income and Leadership Style during the Covid-19 Pandemic on Employee Performance and Their Implications on Operational Performance of Sea Ship Agent Company (Case Study at PT. Harapan Cipta Perkasa) - Arief Supriatna; Edhi Budi Setiawan; Imam Sonny (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic outbreak which has led to the enactment of a central government policy for employees to work from home, both private employees and government employees, so that all systems and parties related to licensing. The delay in the process and the ship's operation to a halt and the ship's departure. This makes company leaders to look for solutions in dealing with these situations because the company is experiencing a decline in revenue, which has an impact on the income of each employee as well. The purpose of this study is to analyze and examine whether a decrease in income will have an impact on employee performance and company operations. The method used in this research is the method of Structural Equation Model (SEM) based on Partial Least Square (PLS). The results of the findings in this study are a partial decrease in income has a positive effect on employee performance and company operational performance but is not significant. Leadership style partially has a positive and significant effect on employee performance and company operational performance.